Belonging, Membership and Mobility in Global History - Dirk Hoerder (Dve Domovini, 2012)
Belonging and membership in societies depend on resources, societal structures, and stateside frames rather than on postulated and essentialized identities. Throughout the ages migrants have changed societies and affiliations; globalization emerged in the 1490s when the tri-continental    African-Asian-European worlds and the dual American continent became connected. Migrants moved translocally or transregionally – the “trans” emphasizes connections across dividing lines or spaces, to continuities cre- ated (or, perhaps, merely mentally constructed) by human agency. This essay approaches the topic from four angles: (1) migrants’“funds of knowledge,”(2) newcomers’“Otherness,”(3) power hierarchies, and (4) connectivity-inclusions-exclusions. In conclusion, belongings of globally mobile men and women will be discussed as transcultural rather than transnational.